2015
DOI: 10.1159/000439244
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Attitudes to the Ethical Issues Raised by the Return of Incidental Genomic Research Findings in Children: A Follow-Up Study

Abstract: Objective: We explore the stability of parental attitudes to the ethical issues raised by the return of genomic research results. Methods: A 19-item questionnaire was mailed to participants in a large genome research consortium 18 months following a baseline survey. We describe the stability of parental attitudes to (a) sharing of genomic research results, (b) endorsement of children in genomic research, (c) responsibilities of researchers, and (d) responsibilities to extended family. We also explore their exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…This prompted retrospective comparison (during data analysis) of SF decisions made at the time of consent. In contrast to a survey study by Fernandez et al,29 which reported no difference in views towards return of SF over an 18-month period, half of our interviewees who felt they would decline SF had originally consented to receive them. This raises questions as to whether their views have since changed or whether the decision at consent was representative of their wishes.…”
Section: Discussioncontrasting
confidence: 92%
“…This prompted retrospective comparison (during data analysis) of SF decisions made at the time of consent. In contrast to a survey study by Fernandez et al,29 which reported no difference in views towards return of SF over an 18-month period, half of our interviewees who felt they would decline SF had originally consented to receive them. This raises questions as to whether their views have since changed or whether the decision at consent was representative of their wishes.…”
Section: Discussioncontrasting
confidence: 92%
“…1-03), or "genetic accident" (mother, no. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The question of the meaning of the result was raised by some parents: "the much talked about gene is called XXXX (the name of the gene), or something During the interview, parents who obtained a diagnosis for their children very often expressed satisfaction (group 1, positive results).…”
Section: Post-es Experiences Of Parents-the Qualitative Studymentioning
confidence: 99%
“…(father, no. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For half of group 1 (positive result), even when a diagnosis was made, a feeling of helplessness and uncertainty persisted.…”
Section: Post-es Experiences Of Parents-the Qualitative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As genomic research may provide clinical findings about both child-onset and adult-onset genetic diseases, it is important to consider the child’s future and right to know and not to know. Respecting the right to an open future means that the child can make his or her own autonomous decisions when reaching adulthood [ 10 , 14 , 27 , 43 , 44 ]. Feinberg [ 45 ] holds that children have a right, while they still are children, to remain ignorant of disease predisposition until they reach adulthood, presumably capable of making a well-informed decision.…”
Section: Discussionmentioning
confidence: 99%